ADA HUBUNGAN YANG BERMAKNA ANTARA SARAPAN PAGI DENGAN INDEKS PRESTASI ANAK SEKOLAH DASAR - Eka Nuryanti, Septi; Induniasih; Lestari, Ratna (MEDIA ILMU KESEHATAN, 2014)
Background: Breakfast is an important meal before doing physical activity on the day. Breakfast could improve children’s attention, memory and information processing while they are studying at schools. Based on the interview conducted in preliminary study, sixout of 10 children said that they sometimes had breakfast, two children said that they rarely had breakfast, and only two children said that they always had breakfast. Objectives: This study aimed to investigate the corelation between breakfast activity with the achievement of school index in students of SD N 1 Pundong Bantul. Methods: This research used observational study design with cross-sectional approach. Samples were recruited by total sample technique, consisted of 43 students. The research instrument was a questionnaire.. Data were analysed using Chi-square. Results: Most of students had good achievement indexes as many as 19 children (44.2%). Most of students had breakfast as many as 24 children (55.8%). The chi-square test showed significance with p-value=0,03 (p<0.05). Conclusion: This study showed that there was a significant correlation between breakfast activity and achievement indexat school. Schools need to provide health education about the benefits of breakfast and motivate students to have breakfast before leaving for school. Key words: Achievement index, breakfast